Models of training race-walkers during the mezocycle of the direct preparation for starts based on the multi-criteria method of the analytic hierarchy process - Sudol, GT.; Adamus, W.; Mleczko, E. (Journal of Kinesiology and Exercise Sciences, 2017)
Aim. In the sports training of the best competitors around the world, there are many ways to organize the direct preparation for a start. This training stage usually determines success. Despite such awareness, there is no knowledge as to which training system model can be considered the best in preparation for the most important sports event. Selection of the most effective variant of a champion`s sports training system in direct preparation for the Olympic Games in the 50 km race-walk. Basic procedures. In our research, we based on the assumptions of the multi-criteria Analytic Hierarchy Process (AHP), which was developed by T.L. Saaty. The goal of the work progressed steadily: the main criteria (training measures, renewal, volume, Substantive structure training, base) were determined and subcriteria were allocated to them. A multi-level structure of the problem was built in the form of a hierarchical tree with respect to the main objective. A special interview with questionnaire was developed utilizing Saaty`s 9-level fundamental comparison scale. These interviews were conducted with 14 coaches of the best athletes in Poland and the world in the 50 km race-walk. It`s the purpose of the study was to defi ne the main criteria and subcriteria within the structure of hierarchical dominance (preferences, weights). The article gives the priority (weight) for all criteria and subcriteria as the geometric average of all the trainers` answers. The subsequent step in fi nding the best way to prepare the athletes for the 50 km race-walk was to develop training models and choose the best alternative. The computer programms Super Decisions and Expert ChoiceTM were used to perform calculations. Results. Among the 5 established criteria, training measures were the highest (Ptr. meas.=0.389) for all experts (coaches). Analysis shows that training in the DPS is the most important criterion. The next two measures (Substantive structure training and base) were given equal priorities (Pmat. str.= PB=0.180). Less important was the volume (Pvol.=0.146), and the least important - renewal (Pren.=0.104). The sum of the priorities is always 1 (100%). The highest global priority was achieved by the PE subcriterion (19.61%). Among the 4 decision alternatives (training models), the best turned out to be the model by the younger-generation Polish coaches. Conclusion. The AHP is an adequate tool that demonstrates the fi ndings well, therefore it may be suitable in choosing the most appropriate training alternative in the direct preparation for a start in the 50 km race-walk.